Extensive and Prolonged Restoration of Dystrophin Expression with Vivo-Morpholino-Mediated Multiple Exon Skipping in Dystrophic Dogs - Yokota, Toshifumi (Mary Ann Liebert, Inc., 2012)
Duchenne muscular dystrophy (DMD) is a severe and the most prevalent form of muscular dystrophy, characterized by rapid progression of muscle degeneration. Antisense-mediated exon skipping is currently one of the most promising therapeutic options for DMD. However, unmodified antisense oligos such as morpholinos require frequent (weekly or bi-weekly) injections. Recently, new generation morpholinos such as vivo-morpholinos are reported to lead to extensive and prolonged dystrophin expression in the dystrophic mdx mouse, an animal model of DMD. The vivo-morpholino contains a cell-penetrating moiety, octa-guanidine dendrimer. Here, we sought to test the efficacy of multiple exon skipping of exons 6–8 with vivo-morpholinos in the canine X-linked muscular dystrophy, which harbors a splice site mutation at the boundary of intron 6 and exon 7. We designed and optimized novel antisense cocktail sequences and combinations for exon 8 skipping and demonstrated effective exon skipping in dystrophic dogs in vivo. Intramuscular injections with newly designed cocktail oligos led to high levels of dystrophin expression, with some samples similar to wild-type levels. This is the first report of successful rescue of dystrophin expression with morpholino conjugates in dystrophic dogs. Our results show the potential of phosphorodiamidate morpholino oligomer conjugates as therapeutic agents for DMD.